Genetic parameters of lactation performance traits in Hariana cattle - S. Singh; Rana, Z.S.; Dhaka, S.S.; Pander, B.L.; Yadav, A.S.; R. Kumar (Journal of Livestock Biodiversity, 2025)
The data pertinent to lifetime hails on 762 Hariana cows calving during 1966 to 2000, progeny of 23 sires maintained at Government Livestock Farm, Hisar were considered. First lactation MY, LL and PY had high positive genetic correlation with fourth lactation MY, LL and PY except the relationship of first lactation length with fourth lactation MY and PY. First lactation DP, CI and SP had high negative genetic correlation with fourth lactation MY, LL and DP barring fourth lactation length association with first SP and CI. First lactation MY and LL had positive correlations with all the fourth lactation performance traits except with fourth dry period. Second lactation MY and PY had high positive genetic correlation with fourth lactation MY and PY, while these traits had negative association with fourth lactation DP, SP and CI. Moreover, third MY, LL and PY had negative genetic correlations with fourth lactation DP, SP and CI barring low and positive association of third LL with fourth SP. In addition to this, third DP, CI and SP had high and negative genetic correlations with fourth lactation MY and PY, while these traits had high positive genetic correlations with fourth DP, CI and SP. This suggested that selection on the basis of PY1 will also bring out genetic improvement in MY of each lactation. This will not only reduce the generation interval by early selection but also reduce the unproductive life of the animal by reducing DP.